DECREASE HYPERTENTION THROUGHT GIVING NONI FRUIT JUICE - Hariati, Hariati (Jurnal Penelitian Keperawatan Medik, 2021)
Hypertension in elderly people in Indonesia is included in the 10 countries with the highest prevalence in the world. This disease is controlled to prevent further complications. The juice of noni (morinda citrifolia) fruit can be used as a provision for lowering blood pressure in elderly people with hypertension in Durin Tonggal village, Pancur batu sub-district. Objective to determine the effect of noni juice on lowering blood pressure in patients with hypertension. A Quasy Experiment study design with a population of 60 elderly with hypertension. The sample was taken by purposive sampling technique of 60 people divided into 15 people. The research instrument was the observation sheet. Data were analyzed with âˆ0.05. The results of the experimental group research showed that the average pre TDS was 150.00mmHg, pre-TDD 90.00mmHg and TDS 200.00mmHG, and TDD 150.00mmHg. The results of the analysis and statistical tests obtained a systolic BP of 0.000 and a diastolic of 0.002 with a P value of <0.05, so Ho is rejectedmeaning that noni juice is effective in reducing blood pressure in the elderly.